Direct regeneration of plant lets from immature inflorescenee of ginger (Zingiber officinale Rosc.) by tissue culture - RAVINDRAN, K NIRMAL BABU, K SAMSUDEEN, P N (Journal of Spices and Aromatic Crops, 1992)
Immature inflorescences of ginger when cultured on MS revised medium supplemented with 10 mg 1-1 BA and 0.2 mgl-1 2, 4-D re ulted in the conversion of floral buds into vegetative buds and these later developed into plantlets dil’,ectly without intervening callus phase. About 38% of the buds produced multiple shoots ranging from 5-25. When individual flowers were cultured separately on the same medium plantlets developed from the ovary in 45% of cases. These plantlets were made to develop good root system on MS medium with 1 mgl-1 NAA. These rooted plantlets established easily in the soil. In some of the cuI tures the ovaries developed into fruits.